Pillar of Fire – from Auschwitz to Casablanca - Davidovitch, Nitza; Dort, Ruth (Journal of Education Culture and Society, 2021)
Aim. This study examines the characteristics of the individuals who go on the journey to Poland, which is a key element of the Holocaust education curriculum in Israel, their personal connection to the Holocaust, as well as the socio-political developments in Israel that attempt to bridge the gap between the various poles in society – between East and West. Concept. Holocaust education includes the formal part, which is the historical narrative, and the informal part, which is the journey to Poland. This study follows the development of Holocaust education and commemoration of the victims of the Holocaust – from the narrative of the Holocaust of the Jews of Europe to the narrative of the Holocaust among the communities of North African descent. Results and conclusion. The findings of the study indicate a link between family support and ties to the Holocaust, and the journey to Poland, which appears to be in line with findings of Nitza Davidovitch and Dan Soen (2011), who found a correlation between the students participating in the journey and their personal connections to the Holocaust, in contrast to students with no family connection with the Holocaust. For all its importance, the journey to Poland has been found to perpetuate social polarisation. Practical applications. The current study highlights the challenge of Holocaust education in order to build a bridge of shared historical destiny through this seminal event of the twentieth century. Originality. This work sparks the question of how to make the journey to Poland a unifying factor in collective national memory.